PROCESS OF MANUFACTURING AN AIRCRAFT PART BY RESIN INJECTION - BECHTEL, STEPHANE; HOCHART, BENOIT; BLOT, PHILIPPE (2012)
The method of fabricating an aircraft part comprises the steps of placing in a stack comprising a preform at least one layer of a material that presents permeability to a predetermined resin that is less than the permeability of a portion of the preform that is the closest to the layer; and placing a resin presence sensor on a side of the layer that is remote from the preform.